PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL: MENGGALI NILAI SPIRITUAL DALAM PERMAINAN PERANG SABUT DI DESA RAMBUTAN MASAM - Agiska Cahnia; Nai’mahtul Zakiyah Dwi Wardhani; Alyada Ulya; Mutmainnah; Wulan Dari; Dea Ayu Anggraini; Walhazwa; Maudy Aprilia; Dini Alya Firda; Ardya Syakibilla Nadine; Nofeni Ramadani; Naffa Asti Aprilia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explores the spiritual meaning embedded in the traditional Perang Sabut game in Rambutan Masam Village, Batanghari Regency, Jambi, as a foundation for character education grounded in local wisdom amid globalization. Employing qualitative ethnographic methods, primary data were gathered through semi-structured interviews with local figures (M. Suhaimi and Samsul Bahri) and participatory observation in February 2026, revealing the game as a collective ritual rich in spiritual significance: smoke from burning coconut husks symbolizes prayers for rain, the no-clothing rule reflects humility and surrender to God, and its post-Quran recitation timing integrates faith with communal bonding.Values such as gratitude, piety, harmony with nature, and mutual cooperation are instilled in children, aligning with the Pancasila Student Profile and Merdeka Curriculum. Adapting this tradition into elementary school learning strengthens moral character against modern cultural erosion, fostering a generation that excels academically, remains devout, and preserves national identity